2013
DOI: 10.1590/s0034-737x2013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Análise da adaptabilidade e estabilidade de produção em ensaios regionais de feijoeiro para o Estado de São Paulo

Abstract: Analysis of adaptability and yield stability in regional trials of common bean for the state of São Paulo, BrazilThe objective of the present study was to identify superior genotypes for yield, adaptability and stability in common bean yield using the Lin & Binns (1988) analysis modified by Carneiro (1998). Twenty-two genotypes were analyzed from the main Brazilian plant breeding programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
(15 reference statements)
0
13
0
1
Order By: Relevance
“…The coefficients of variation (CVs) were low (7.5 ~ 14.1%), indicating good experimental accuracy and reliability of results. In studies with common bean, Oliveira et al (2006), Silva et al (2013), Menezes Júnior et al (2013) and Domingues et al (2013), found CVs between 6-23% for grain yield. The grain yield varied between experiments and means were highest in the dry and winter seasons in Coimbra (3571 and 3153 kg ha -1 , respectively).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The coefficients of variation (CVs) were low (7.5 ~ 14.1%), indicating good experimental accuracy and reliability of results. In studies with common bean, Oliveira et al (2006), Silva et al (2013), Menezes Júnior et al (2013) and Domingues et al (2013), found CVs between 6-23% for grain yield. The grain yield varied between experiments and means were highest in the dry and winter seasons in Coimbra (3571 and 3153 kg ha -1 , respectively).…”
Section: Resultsmentioning
confidence: 96%
“…In common bean, Dalla Corte et al (2002), Carbonell et al (2004, Oliveira et al (2006), Pereira et al (2009), andSilva et al (2013), among others, carried out research of this nature. However in these studies, most genotypes tested were lines of a particular breeding program, which were often not released on the market.…”
Section: Introductionmentioning
confidence: 99%
“…A significant C x E interaction has previously been described for flowering (Mambrin et al, 2015), cycle Ribeiro et al, 2004Ribeiro et al, , 2014, insertion of the first pod (Ribeiro et al, 2014;Maziero et al, 2015), and grain yield (Elias et al, 2007;Melo et al, 2007;Rocha et al, 2010;Pontes Júnior et al, 2012;Domingues et al, 2013;Silva et al, 2013;Pereira et al, 2009aPereira et al, ,b, 2010Pereira et al, , 2014Barili et al, 2015a,b) in experiments evaluating the performance of common bean cultivars. The existence of a significant C x E interaction indicates that the stability analyses may be useful for the identification of superior cultivars.…”
Section: Joint Analysis Of Variancementioning
confidence: 81%
“…The stability of common bean grain yield has been extensively evaluated using the Eberhart and Russell (1966), Lin and Binns (1988), and additive main effect and multiplicative interaction (AMMI) methods (Carbonell et al, 2007;Melo et al, 2007;Pontes Júnior et al, 2012;Domingues et al, 2013;Silva et al, 2013;Pereira et al, 2009aPereira et al, ,b, 2014Barili et al, 2015a,b). Cycle stability in common bean has been studied using the Eberhart and Russell (1966) method, although few environments were considered (Ribeiro et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Porém, a análise de estabilidade e adaptabilidade é uma alternativa para amenizar os efeitos da interação e identificar cultivares com comportamento previsível e responsivas às melhorias do ambiente (CRUZ & REGAZZI, 2001). Tal estimação fornece informações detalhadas sobre o comportamento das cultivares e contribui na sua caracterização quanto à resposta às variações ambientais, proporcionando maior segurança na recomendação (SILVA et al, 2013).…”
Section: Introductionunclassified